Post consolidation performance of the Nigerian Banks - Nwosu, Chidiebere Ezechi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: Nigeria, like every other legitimate nation operates an open economy which gives rise to financial liberalization, opening the economy to the global financial market which has exposed the fragility and vulnerability of her financial system. It became inevitable for the Central Bank of Nigeria introducing measures that would enhance the financial system stability of the nation, and also reduce the exposure to the global financial danger. This study therefore investigates the post consolidation performance of the Nigerian banks in comparison with the pre-consolidation era, with the aim of finding out if the consolidation is of any benefit. We employed secondary data obtained from bank scope annual report. The data were analyzed using techniques such as T- test and random effect regression analysis. The independent variable used were Return on Assets (ROA) and Return on Equity (ROE) which were significant, meaning that is a statistical difference between the pre and post consolidation era of the Nigerian banking system. The study recommends that before setting up a minimum capital for banks, the CBN should look at considerations from all facet of the economy so as to make significant impact. Our work advises the bank executives to embark on routine training and retraining of staff as well as proper handling of post consolidation challenges. Also, earnings on total assets should be maximized through outsourcing the bank’s surplus total assets by the management. Keywords: Consolidation, Liquidity, Regression, Capital adequacy, Asset quality ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Nijerya her açık ekonomi uygulaması olan yasal ülkede olduğu finansal serbestleşmeye önem vermektedir. Bu yüzden merkez bankasının finansal sistemin istikrarı için bazı önlemler alması kaçınılmazdır. Merkez bankası yönetimi varolan bankaların güçlenmesi ve yeni bankaların da iyi bir başlangıç yapması için 25 milyar Nairalık sermaye ayırmıştır. Bu çalışmanın amacı Nijerya bankalarının konsolidasyon sonrası ve öncesi performanslarını karşılaştırarak konsolidasyonun yararını araştırmaktadır. Veriler Bankscope yıllık raporlarından elde edilmiştir. Analizlerde T-test ve rastgele etki regresyonu yöntemi kullanılmıştır. Bağımlı değişken olarak varlık üzerinden getiri ve sermaye üzerinden getiri kullanılmış ve bu değişkenler istatistiksel olarak anlamlı çıkmıştır. Bu da Nijerya bankacılık sisteminde konsolidasyon öncesiyle sonrasının istatistiksel olarak farklı olduğunu kanıtlamaktadır. Bu çalışmanın sonucunda banka yöneticilerine, çalışanlarını konsolidasyon sonrası yaşanan zorluklara karşı eğitim vermelerini öneriyoruz. Bunun yanında varlık getirisini maksimize etmeleri gerekmektedir. Anahtar Kelimeler: Konsolidasyon, likidite, regresyon, sermaye yeterliliği, aktif kalitesi.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2013. Supervisor: Assoc. Prof. Dr. Eralp Bektaş.
Keywords: Banking and Finance; Banks and Banking - Nigeria; Consolidation Liquidity Regression Capital Adequacy Asset Quality